Uso del extracto de pituitaria de paiche (EPP), en la reproducción inducida de Brycon amazonicus (Agassiz, 1829) "sábalo cola roja" - Ruiz Tafur, Kevin Morgan (2021)
The objective of the study was to determine the efficacy of paiche pituitary extract (EPP) in the induction of Brycon amazonicus "red-tailed tarpon". 27 pairs of B. amazonicus were used (1.94 ± 0.24 kg of weight and 50.78 ± 2.22 cm of length in males and 2.28 ± 0.38 kg of weight and 49.32 ± 11, 39 cm in length in females). The hormonal inducers of EPP (10% and 90% of the total) will be applied in two doses, with an interval of 12 hours. Three hormonal doses of EPP are applied, in the case of females: T1: 3.0 mg/kg, T2: 4.0 mg/kg and T3: 5.5 mg/kg. In males: T1: 0.5 mg/kg, T2: 1.0 mg/kg, T3: 1.5 mg/kg. The females induced with EPP responded positively to ovulation, finding significant differences (P<0.05), with T1 and T2 reaching the best ovulation rates with 77.73% and 88.87% respectively, regarding the hatching rate, differences were also found. T2 the best with 40.21%. The males of B. amazonicus induced with EPP, responded positively to spermation, obtaining 88.87%, this value being the same for T1 and T2, with respect to sperm quality, the variable seminal volume showed differences where T3 showed greater volume with 20 ml in On average, differences were observed with respect to sperm concentration and spermatocrit, with a higher dose of EPP application decreasing sperm concentration and spermatocrit. According to the results obtained, the dose of 4.0 mg/kg of EPP (T2) is recommended, since it had positive effects on ovulation and hatching rate. On the other hand, all doses responded to spermiation but the dose of 0.5 mg/kg (T1) is the best due to the high values of sperm concentration and spermatocrit.